Shedding light on endometriosis: Patient and provider perspectives on a challenging disease. Issue 2 (June 2020) - Zale, Madalene; Lambert, Emily; LaNoue, Marianna D; Leader, Amy E
Background: Endometriosis is a serious yet understudied medical condition impacting millions of women worldwide. Methods: This mixed-methods study aimed to understand healthcare provider perceptions and patient experiences with endometriosis in the United States. Providers were surveyed to assess their understanding of disease prevalence. A subset of providers also participated in short, open-ended interviews about treating patients who have or are suspected to have endometriosis. Interviews were also conducted with women diagnosed with endometriosis to understand their experiences with the disease. Means and frequencies were calculated for survey data; interviews were transcribed and separately analyzed by two coders using an iterative coding process until agreement was reached. Results: Fifty-three providers completed surveys. Of the 53 providers, 6 (11%) accurately identified the prevalence of endometriosis. Four providers and 12 patients completed interviews. Emergent themes among providers included limited training, difficulty of diagnosis, complexity of the referral process, a challenging patient–provider dynamic, and the importance of multidisciplinary collaboration. Emergent themes from patients included the psychological impact of the disease, difficulties interacting with the healthcare system, self-advocacy, quality of life, and limited treatment options. Conclusion: Providers are frequently unfamiliar with the far-reaching scope of endometriosis and cite many challenges caring for patients with the disease. Patients equally find the disease challenging to live with as it encroaches on physical, mental, and emotional well-being.